HUMIC ACID FILTRATION EFFICIENCY OF POLYPROPYLENE-BASED ULTRAFILTRATION MEMBRANES - Sri Mundarti; Rahma Amalia; Rara Ayu Lestari; Nita Widyastuti (Fakultas Teknik Universitas Wahid Hasyim, 2025)
Polypropylene (PP) membranes exhibit advantageous characteristics for filtration processes, including chemical resistance, thermal stability, hydrophobicity, low cost, and mechanical durability, making them well-suited for long-term applications in water treatment, particularly for removing organic compounds. This study aims to evaluate the performance of hollow fiber PP membranes in the ultrafiltration of humic acid solutions, serving as a model organic contaminant. The experimental setup involved filtering a 15 mg/L humic acid solution in demineralized water at 1 bar for 120 minutes. Performance evaluation focused on three parameters: pure water flux, humic acid permeate flux, and rejection efficiency. The initial pure water flux reached 72 L/m²·h, decreasing to approximately 57 L/m²·h within the first 20 minutes, indicating membrane compaction. The humic acid permeate flux declined from 42 to 33 L/m²·h, attributed to fouling caused by physical and chemical interactions between humic acid and the PP membrane surface. Rejection efficiency dropped from an initial 90% to 75% by the end of the process. The observed performance degradation was linked to adsorption, pore blocking, and concentration polarization. Despite their structural advantages, PP membranes are prone to organic fouling; therefore, surface modification and feedwater pretreatment are recommended to optimize long-term performance.